(untitled) (Global Journal of Management and Business Research, 2014)
Alibaba has become the largest online and mobile commerce company in the world in just a few years and barely anyone expected it to be so successful. It has provided numerous business opportunities for small and medium enterprises to leverage the innovative technology to compete more efficiently domestically and globally. This study does not attempt to describe Alibaba as a perfect business; rather it discuss the marketing strategies, promotion, distribution channels and some important lessons that were carried out by Jack Ma to achieve success in this complex world of online trading. In this literature review, we examine a few key factors of Alibaba’s success such as its specific marketing strategies, various challenges, its strong branding image, superior customer value proposition, better shopping experience, huge sales volume and economies of scale.